Prevalência e fatores associados a lesões labiais e periorais decorrentes da exposição solar em trabalhadores de praia - Lucena, Eudes Euler de Souza (2011)
This study aimed to verify the prevalence of lip and perioral lesions in worker who were under sunshine on the beaches of Natal/RN and to investigate possible associations of these with sociodemographic, occupational and general health variables. For this, 362 individuals who had one of the urban beaches (Ponta Negra / Environment / Redinha) in the city of Natal/RN as a working environment in the study. We excluded people under 18 years old. Data collection was done through epidemiological analysis and extra-oral validated questionnaire with questions that characterize socioeconomic and demographic factors, occupational exposure and general health. The male subjects (72.6%) were the majority in the sample. The people who worked directly exposed to high peaks of ultraviolet radiation, as well as informal workers predominated. Considering the total sample of individuals, ephelides in the perioral region (33.7%) and labial region (24.0%), solar lentigo perioral (15.2%) and actinic cheilitis (13.8%) stood out as the most prevalent lesions. Indoor workers and those who had a habit occurrence of injuries by 19% and 21% respectively higher when compared to outdoor workers and people without habits. The variable use of cap / hat was associated with the presence of cold sores (Qui2 = 1,328, p = 0,058). On the threshold of significance, the type of work was also associated with lesions in lip occurrence (p = 0,042). Men showed a lower incidence of perioral lesions when compared to female workers (PR=0,716, p valor = 0,002). The present study showed high prevalence of lip and perioral lesions. The premalignant lesions were the most identified, both as in lip skin. It is important therefore to be encouraged to adopt protective measures against excessive sun exposure, fairly and consistently